2021
DOI: 10.1002/tafs.10304
|View full text |Cite
|
Sign up to set email alerts
|

Spawning Intervals, Timing, and Riverine Habitat Use of Adult Atlantic Sturgeon in the Hudson River

Abstract: The Hudson River currently supports the largest population of Atlantic Sturgeon (Acipenser oxyrinchus oxyrinchus) in the United States despite currently supporting less than a percent of historic abundance. Listed as Endangered throughout much of their range, Atlantic Sturgeon are still impacted by multiple threats, resulting in habitat destruction or direct mortality that has inhibited a population rebuild despite 20+ years without directed fishing pressure. To assist in management and reduction in anthropoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(30 citation statements)
references
References 27 publications
0
28
0
Order By: Relevance
“…Spawning periodicity may also play a role in year-class strength. Estimates of spawning intervals for female Atlantic Sturgeon are variable, ranging from 1 to 5 years (Hilton et al 2016;Hager et al 2020;Breece et al 2021). The higher catch rates that have been observed in recent years (2012, 2015, and 2018) occurred in 3-year intervals, and the length distribution in these years indicated a greater proportion of presumed age-3 individuals.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Spawning periodicity may also play a role in year-class strength. Estimates of spawning intervals for female Atlantic Sturgeon are variable, ranging from 1 to 5 years (Hilton et al 2016;Hager et al 2020;Breece et al 2021). The higher catch rates that have been observed in recent years (2012, 2015, and 2018) occurred in 3-year intervals, and the length distribution in these years indicated a greater proportion of presumed age-3 individuals.…”
Section: Discussionmentioning
confidence: 98%
“…2020; Breece et al. 2021). The higher catch rates that have been observed in recent years (2012, 2015, and 2018) occurred in 3‐year intervals, and the length distribution in these years indicated a greater proportion of presumed age‐3 individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Atlantic Sturgeon appear to exhibit a subdivided metapopulation structure along the Atlantic coast, with high philopatry among spawning adults leading to genetically distinct populations among river systems (ASMFC 2017; White et al 2021). Historical accounts suggest that spawning intervals range from 3 to 5 years for females and from 1 to 5 years for males (Smith 1985); however, recent studies suggest that spawning may be more frequent in some systems (Hager et al 2020; Breece et al 2021). Timing of spawning varies latitudinally, with upriver migrations beginning as early as March in southern climates and as late as July for more northerly populations (Dadswell 2006; Hilton et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The changes in salinity could alter their distribution and spawning grounds as well as larval survival and consequent recruitment. Conversely, Atlantic sturgeon, an endangered species in the HRE, spawn upstream from the tidal salt front as their spawning grounds (Van Eenennaam et al, 1996;Breece et al, 2021) and their early life stages are intolerant to saline conditions (Kazyak et al, 2020). Van Eenennaam et al (1996) indicated that the eggs and larval dispersal strategy of Atlantic sturgeon may require the environmental conditions remain freshwater throughout the spawning season.…”
Section: Impacts Of Salinity On Physiology and Spawning Groundsmentioning
confidence: 99%